Música e adulto de meia-idade: um estudo sobre trajetórias musicais e motivação - Gama, Francy Dias Holanda (2016)
This research had to objective to analyze the musical path of middle-aged adults, given the motivation to experience the music in this stage of life, and aimed to understand how the cultural, economic and social factors have worked in their life trajectories. These subjects are defined as persons who are between 40 and 65 years of age, according Papalia. Bourdieu was the principal author used for data analysis. The methodology used was a qualitative approach based on the use of narrative originated the autobiographical method. The collected narratives resulted in loaded life stories of musicality and emotions, allowing the perception that the Cultural Capital is one of the determining factors for the middle-aged adult choice experiencing music at this stage of life, interfering with the individual trajectories.